Innate immune response: ally or enemy in cutaneous leishmaniasis?. Issue 5 (26th May 2021) - Serrano-Coll, Héctor; Cardona-Castro, Nora; Ramos, Ana Pilar; Llanos-Cuentas, Alejandro
ABSTRACT: Cutaneous leishmaniasis (CL) is an infectious and neglected disease caused by parasites of the genus Leishmania, which produces a wide spectrum of cutaneous manifestations. CL research has shown that the innate immune activity of cells such as neutrophils, natural killers, macrophages, dendritic cells and the complement system are capable of controlling this infection. However, Leishmania can also modulate the immune activity of these cells to promote its own survival and proliferation at the intracellular level. This review discusses the role of the innate immune response in the control and spread of this infection. Abstract : This manuscript is the product of an effort to understand the role of the immune response in the control and spread of this infection that is a public health issue in 98 countries around the world.